METAFORA DALAM RAGAM BAHASA PUISI (PENDEKATAN TEORI COGNITIF LINGUISTIK) - Rizka Hayati (LPPM Universitas Pekalongan, 2016)
Metaphor is something that is commonly used in poem. The use of metaphor in poem can give the poem a deeper meaning and understanding. Thus, metaphor in poem becomes phenomena which is interesting to be analyzed. From the background above, the writer is interested in analyzing the use of metaphor in poem. The objective of this study is to find out metaphors in poems and interpret the meaning. This study analyzes the meaning of metaphor by using cognitive linguistics approach. The object of the study is poem “Aku” and “Karawang Bekasi” by Chairil Anwar and